Leisure time physical activity, liver fat and cardio-metabolic risk factors : a monozygotic co-twin control and an observational study - Giarmenitis, Dimitrios (2019)
Introduction: Obesity has a strong link with cardio-metabolic risk factors. This fact has raised the necessity to understand the underlying causes of obesity for efficient prevention and treatment strategies. It has been demonstrated that the distribution of the fat in ectopic fat depots, such as liver and viscera, associates with features of the metabolic syndrome (MS) and an increased risk for manifesting cardiovascular diseases. Interestingly, MS can be present regardless obesity-defined anthropometric measurements. Hence, abnormal fat content in ectopic fat depots is deemed to increase the risk for developing the cardio-metabolic risk factors in non-obese population. A non-pharmacological method for maintaining physiological quantity of fat in ectopic fat depots is physical activity. Based on the aforementioned, the aim of this study was initially to examine the independent effect of chronic leisure-time physical activity (LTPA) on the intrahepatic triglyceride (IHTG) content. The second aim was to test the association of the IHTG with variables of LTPA, anthropometrics, blood lipids, blood pressure, glucose homeostasis as well as abdominal adipose tissue in healthy non-obese young adults prior to overt cardio-metabolic diseases. Methods: Twenty-three apparently healthy monozygotic (MZ) twin pairs (N=46, mean age= 34 years, range 32-36) had been assessed retrospectively regarding their LTPA level in the FITFATTWIN study. All the subjects were tested for the IHTG content by analyzing magnetic resonance images (MRI) of the liver, the MS criteria as well as variables of the abdominal adipose tissue. For the first aim of the study, ten of those MZ twin pairs (N=20) with the greatest LTPA discordance were divided into two groups of “active” and “inactive” co-twins. We performed a comparison of difference in the IHTG content between the “active” and “inactive” group. In the latter analysis, due to the twinship, both the genetic background and the childhood environment were controlled. Therefore, we examined the independent effect of LTPA on IHTG content. In regard to the second aim, an individual-based correlation analysis of 22 pairs (46 volunteers) was conducted between the IHTG content and retrospectively-tested LTPA indexes, the MS criteria and the abdominal adipose tissue. Results: The comparison between the two groups, concerning the IHTG content, exhibited no statistically significant difference although the average IHTG content tended to be lower in the “active” co-twin group. The individual-based association analysis revealed statistically significant correlations between IHTG content and anthropometrics, abdominal adipose tissue, and glucose homeostasis variables. More specifically, IHTG content correlated with BMI (r=0.313, P=0.006), waist circumference and (r=0.396, P=0.034), and total fat percent (r=0.397, P=0.006). Furthermore, IHTG content associated significantly with the visceral adipose tissue (VAT) (r=0.465, P=0.001) and with the subcutaneous adipose tissue (SAT) r=0.350 (P=0.017). The value of the 30min time point of the oral glucose tolerance test was also related with the IHTG content (r=0.348, P<0.05). IHTG content did not associate neither with LTPA indexes nor with blood pressure. Conclusion: Previous findings have supported the notion that chronic LTPA can act as an independent effect on health variables which associate with cardio-metabolic lesions. The MZ co-twin study aimed to examine the potential causal association between the liver fat and LTPA. The findings of this did not show significant difference on the IHTG content between the groups with the LTPA discordance potentially because subjects were healthy young adults with averagely normal values of IHTG deposition. In the individual-based association analysis, the IHTG deposition correlated with some cardio-metabolic risk factor. It was demonstrated that the higher the IHTG content the higher the values of the measured factors. Even though these associations do not imply causality the results agree with the literature concerning the role of liver fat on the exacerbation of the cardio-metabolic risk factors.